Bibliometric-Based Needs Analysis of Comic-Based Multiple Representation Learning Media on Thermochemistry - Avra Buana Larasati; Isana Supiah Yosephine Louise (Indonesian Journal of Chemical Education, 2026)
Thermochemistry presents considerable learning challenges because students must simultaneously interpret energy changes at the particle level and relate them to observable phenomena and symbolic notations. Such cognitive complexity often leads to low motivation and difficulties constructing coherent conceptual understanding. In alignment with the Merdeka Curriculum, learning media in chemistry should therefore emphasize visual clarity, contextual learning experiences, and active student engagement. However, instructional comics that are widely used in classrooms typically highlight narratives and illustrations without fully accommodating the integration of macroscopic, submicroscopic, and symbolic representations. This study aims to identify research needs for the development of comic-based multiple representation learning media in Thermochemistry by examining publication trends in recent chemistry education research. A bibliometric approach was applied to analyze 295 scientific articles using keyword co-occurrence mapping in VOSviewer. The results show that Thermochemistry, multiple representations, learning media, and educational comics are recurring topics of interest, yet they tend to appear in separate thematic clusters with minimal conceptual linkage. These patterns indicate that research integrating the four domains remains limited. Thus, the findings provide strong justification for the future development of comic-based learning media that explicitly support representational transitions to enhance students’ conceptual understanding of Thermochemistry.